Monetary-fiscal policy interaction and fiscal inflation: A tale of three countries - Martin Kliem; Alexander Kriwoluzky; Samad Sarferaz (ETH Zurich, KOF Swiss Economic Institute, 2015)
We study the impact of the interaction between fiscal and monetary policy on the low-frequency relationship between the fiscal stance and inflation using cross-country data from 1965 to 1999. In a first step, we contrast the monetary-fiscal narrative for Germany, the U.S. and Italy with evidence obtained from simple regression models and a time-varying VAR. We find that the low-frequency relationship between the fiscal stance and inflation is low during periods of an independent central bank and responsible fiscal policy and more pronounced in times of high fiscal budget deficits and accommodative monetary authorities. In a second step, we use an estimated DSGE model to interpret the low-frequency measure structurally and to illustrate the mechanisms through which fiscal actions affect inflation in the long run. The findings from the DSGE model suggest that switches in the monetary-fiscal policy interaction and accompanying variations in the propagation of structural shocks can well account for changes in the low-frequency relationship between the fiscal stance and inflation.
Keywords: E42; E58; E61; 330; Time-Varying VAR; Inflation; Public Deficits